2014
DOI: 10.9790/0837-19775560
|View full text |Cite
|
Sign up to set email alerts
|

Income Benefits of Moringa vis-à-vis Other Leafy Vegetables to Female Traders in Jalingo Markets, Taraba State, Nigeria

Abstract: This study compared the financial benefits of female traders obtained from Moringa oleifera with that from other leafy vegetables in Jalingo Local Government Area markets. It also identified challenges of trade in Moringa leaves in the area. Data collected from 120 respondents through a semi-structured questionnaire were analyzed using Prioritization matrix, Gross Margin (GM) analysis, and ANOVA. Daily mean Gross Income (GI) from Moringa leaves (NGN1127.84) and Amaranthus (NGN503.84) ranked first and second re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The results on estimated monthly income generated (Table 2) LGA may be as a results of competition in the market as there was availability of the produce and many buyers were on ground to purchase the leaves, compare to other markets that had limited supply of the produce. Terver, et al [2] in their study found out that trade in moringa garnered more income compared to other leafy vegetables in Jalingo markets, Taraba State.…”
Section: Estimated Monthly Income Of Traders From Marketing Of Moringmentioning
confidence: 96%
See 4 more Smart Citations
“…The results on estimated monthly income generated (Table 2) LGA may be as a results of competition in the market as there was availability of the produce and many buyers were on ground to purchase the leaves, compare to other markets that had limited supply of the produce. Terver, et al [2] in their study found out that trade in moringa garnered more income compared to other leafy vegetables in Jalingo markets, Taraba State.…”
Section: Estimated Monthly Income Of Traders From Marketing Of Moringmentioning
confidence: 96%
“…The study population comprised all the traders marketing Moringa oleifera (Lam) leaves in Taraba State, Nigeria. A multi-stage sampling procedure was adopted for the study in line with the work of Terver, et al [2]. Stage 1: ten…”
Section: Study Population Sampling Procedures and Sample Sizementioning
confidence: 99%
See 3 more Smart Citations